O Direct Trade no agronegócio café: uma perspectiva de seus agentes - Reis, Nilmar Diogo dos (2018)
The coffee agribusiness presents innumerable agents that permeate a productive chain. On this perspective, Direct Trade recently emerged as a negotiation model between coffee grower and roaster/coffee shops, specifically targeted at the commercialization of specialty coffees, eliminating intermediary agents in the negotiation of coffees. Based on the concepts of "Coffee Waves", Direct Trade is massively used to acquire such high quality coffees and aims to provide a mutual relation between the agents in the chain. Work focused on this theme has presented a considerable growth within the academy, however, focused more on the quality and consumption of grains. By turning specifically to the negotiation actions of specialty coffees among these agents, incipient studies appear in the academic roll that seek glimpses of the interactions between coffee growers and roasters. In this way, there are questions that will guide the proposal of this work and have as objective to analyze, through the theory of the Transaction Cost Economics (TCE), which assumptions lead the coffee growers, as well as the roasters and coffee shops, to act through Direct Trade and analyze the characteristics of these agents, the way they carry out their transactions, as well as the institutional environment where the special coffees are commercialized and finally to investigate how the agents' actions impacts the transaction costs and propose measures to reduce t hese costs. This research was developed in two stages: the first one was a bibliographical research in academic texts (and not academic ones as well) and literature review on the theory used in order to consolidate the concepts and then, to deepen in the second part that consists of semistructured interviews with agents of coffee agribusiness chain who use Direct Trade to make their transactions - Brazilian coffee growers; roasters and/or coffee shops, both in Brazil and abroad. Through the interviews, TCE corroborated the understanding that Direct Trade is a business model aimed at minimizing coffee intermediaries, but presents very different perspectives among Brazilian coffee growers in the face of the perspectives of roasters and/or coffee shops both in Brazil and as well abroad. Although Direct Trade is not a certification such as the FairTrade, Rainforest Alliance, among others, it has also been observed that, although Direct Trade acquisitions do not require or occur through certifiers (Certifications), coffee growers who have improved quality of their coffee, have some type of certification, but not every certified coffee grower operates in the specialty coffee market; or even know the quality of their coffee, which creates an institutional environment without significant changes, permeated with opportunistic actions of its agents due to the limited rationality rooted in the traditional ways of marketing coffee. The research also identified that even without the nexus of contracts signed between coffee growers and roasters and/or coffee shops; it was possible to obtain high amounts paid to the producers for sack of specialty coffees, which have strengthened the expansion of production and sale of specialty coffees via Direct Trade, both in the domestic market and as well abroad.